MENINGKATKAN KEPUTUSAN PEMBELIAN KONSUMEN CAFE MELALUI SELF ACTUALIZATION, WORD OF MOUTH DAN HANGOUT LIFESTYLE - Fietroh, Muhammad Nur (Samalewa: Jurnal Riset & Kajian Manajemen, 2023)
This research aims to examine the influence of self-actualization, word of mouth and hangout lifestyle on purchasing decisions in the millennial generation. This research uses quantitative methods with a descriptive approach. The data collection method uses a questionnaire. The sampling method used purposive sampling and the sample used was 100 people. Data were analyzed using multiple regression analysis, partial hypothesis testing (t test), coefficient of determination testing (R2) using the SPSS application. The results of the t test in this research showed that the partially of self actualization, word of mouth and hangout lifestyle had a positive and significant effect on purchasing decisions of the millennial generation at Kedai Victoria Sumbawa Besar. The independent variables consisting of the self-actualization variable, the word of mouth variable and the hangout lifestyle variable had an influence on the purchasing decision variable was 65.9%, while the remaining 34.1% is influenced by other variables not examined in this research, such as product quality, promotions, price perception, cafe atmosphere, service, etc.